Dynamics and control of gear upshift in automated manual transmissions. (1st January 2013) - Gao, Bingzhao; Lu, Xiaohui; Chen, Hong; Lu, Xintian; Li, Jun
Automated Manual Transmission (AMT) is suitable for heavy-duty vehicles to offer an easy drive and good fuel efficiency. After the dynamics and control problems of gear upshift of AMT are described in detail, Model Predictive Control (MPC), together with a shaft torque observer, is adopted to address these challenging control problems. It is demonstrated through simulations that by using the proposed control scheme of gear shifting, a very short torque interruption time can be achieved, while the shift shock is kept small enough.